An implementation of blazeds technology on TM module - Yong, Jia Hui (2008)
The NX project is proposed by SCAN Associates Berhad (SCAN), with the aim of enhancing the previous version of network security solution by using the latest technologies. TM is one of the NX project’s modules and expected to obtain a better performance in terms of interactivity between the system and the user, and the data transferring time. During internship, some research activities had taken place. The studies include several open source applications namely, Adobe Flex platform, BlazeDS Remoting and Messaging technology, JBoss application server and MySQL relationaldatabase. The methodology used in this project is Rational Unified Process (RUP). RUP is an iterative software development process. Requirements are segregated into several cycles or iterations and each of the iterations will go through the whole process in waterfall life cycle. During the inception and elaboration phases, three types of documents based on Software Engineering methods and standards are produced, which are System Requirement Specification (SRS), System Architecture Design (SAD) and NX TM Module Test Cases. These documents are derived from the company’s proprietary documentation guideline. Due to complexity of the project, the internship durations is insufficient to undergo the construction and transition phases. This project is an intellectual property of SCAN, hence the usage of abbreviation in project’s title (NX) and project’s modules (TM) is an inevitable.